1976
DOI: 10.1042/bj1590585
|View full text |Cite
|
Sign up to set email alerts
|

The stability, polyadenylic acid content and ribonucleoprotein form of nulcear ribonucleic acid in artichoke

Abstract: A nuclear preparation, containing 60-80% of the total tissue DNA and less than 0.5% of the total rRNA, was used to characterize the nuclear RNA species synthesized in cultured artichoke explants. The half-lives of the nuclear RNA species were estimated from first-order-decay analyses to be: hnRNA (heterogeneous nuclear RNA) containing poly(A), 38 min; hnRNA lacking poly(A), 37 min; 2.5 X 10(6)-mol. wt. precursor rRNA, 24 min; 1.4 X 10(6)-mol.wt. precursor rRNA, 58 min; 1.0 X 10(6)-mol.wt. precursor rRNA, 52 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1982
1982

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Therefore, the incorporation of 32Pi was used as a measure of precursor rRNA synthesis in control and auxin-treated artichoke explants. Chapman and Ingle (4) concluded that since the accumulation of radioactivity into DNA appeared linear after 60 min, the specific radioactivity of the nucleotide precursor pool must be approximately constant at this time. Figure 3A, showing the specific radioactivity of DNA throughout the labeling period, verifies their finding.…”
Section: Accmutionmentioning
confidence: 99%
“…Therefore, the incorporation of 32Pi was used as a measure of precursor rRNA synthesis in control and auxin-treated artichoke explants. Chapman and Ingle (4) concluded that since the accumulation of radioactivity into DNA appeared linear after 60 min, the specific radioactivity of the nucleotide precursor pool must be approximately constant at this time. Figure 3A, showing the specific radioactivity of DNA throughout the labeling period, verifies their finding.…”
Section: Accmutionmentioning
confidence: 99%